Is technology making us sick? : a Primer for the 21st Century - Douglas, Ian, 1950- (Big idea (Thames and Hudson), 2020)
Modern technology has enhanced our lives in numerous ways - we can now communicate in real time with friends and colleagues around the world, and do our shopping and banking without leaving home. But, as technology crowds further into our personal lives, is it doing us more harm than good? Are we becoming anxious, depressed and socially isolated, unaware of the manipulating influence of algorithms designed to keep us engaged and to filter the picture of the world we see? Has our online gaming or gambling unwittingly developed into a disturbing addiction? This rigorous and insightful volume assesses the impact of our increased screen time and daily interactions with personal technology on our individual choices, our relationships, and our mental and physical health, and suggests how best to mitigate any adverse effects.